An empirical study on the maintenance of source code clones - Thummalapenta, Suresh (Empirical Software Engineering, 2010)
Code cloning has been very often indicated as a bad software development practice. However, many studies appearing in the literature indicate that this is not always the case. In fact, either changes occurring in cloned code are consistently propagated, or cloning is used as a sort of templating strategy, where cloned source code fragments evolve independently. This paper (a) proposes an automatic approach to classify the evolution of source code clone fragments, and (b) reports a fine-grained analysis of clone evolution in four different Java and C software systems, aimed at investigating to what extent clones are consistently propagated or they evolve independently. Also, the paper investigates the relationship between the presence of clone evolution patterns and other characteristics such as clone radius, clone size and the kind of change the clones underwent, i.e., corrective maintenance or enhancement.